2020
DOI: 10.1073/pnas.2006299117
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus hemagglutinin-esterase and spike proteins coevolve for functional balance and optimal virion avidity

Abstract: Human coronaviruses OC43 and HKU1 are respiratory pathogens of zoonotic origin that have gained worldwide distribution. OC43 apparently emerged from a bovine coronavirus (BCoV) spillover. All three viruses attach to 9-O-acetylated sialoglycans via spike protein S with hemagglutinin-esterase (HE) acting as a receptor-destroying enzyme. In BCoV, an HE lectin domain promotes esterase activity toward clustered substrates. OC43 and HKU1, however, lost HE lectin function as an adaptation to humans. Replaying OC43 ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 81 publications
(104 reference statements)
1
68
0
1
Order By: Relevance
“…The lectin domain of the HEs probably evolved to recognize O-acetylated glycans rich in the mucus layer of the host. It contributes to virion attachment, but also regulates the sialate-O-acetylesterase activity of HE to destroy decoy receptors to facilitate virion migration through the mucus and the release of viral progeny 34,35 . As a main function, the spike protein has to bind to a cell surface receptor to promote virion uptake followed by membrane fusion and ultimately release of the nucleocapsid into the cytoplasm 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lectin domain of the HEs probably evolved to recognize O-acetylated glycans rich in the mucus layer of the host. It contributes to virion attachment, but also regulates the sialate-O-acetylesterase activity of HE to destroy decoy receptors to facilitate virion migration through the mucus and the release of viral progeny 34,35 . As a main function, the spike protein has to bind to a cell surface receptor to promote virion uptake followed by membrane fusion and ultimately release of the nucleocapsid into the cytoplasm 36 .…”
Section: Resultsmentioning
confidence: 99%
“…As a main function, the spike protein has to bind to a cell surface receptor to promote virion uptake followed by membrane fusion and ultimately release of the nucleocapsid into the cytoplasm 36 . Owing to promiscuity, a spike may also have affinity for decoy receptors in the mucus, and for BCoV and OC43 it has been shown that the HE and spike function as a two-component system for dynamic receptor interactions 35 . The binding selectivities of the HEs for specific O-acetylation forms correlate well with the sialic acid repertoire of the mucus of the respective hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, HCoV-229E and HCoV-NL63, in analogy to other betacoronavirus, use a protein receptor 102,103 . Biochemical and crystallographic analyses indicated that, since the shift to the human host, the spike and HE proteins of HCoV-OC43 have co-evolved to optimize the balance between binding and release from sialoglycans in human airways 60,104 . We con rm herein the previously observed emergence of spike and HE variants over time and the replacement of earlier variants with the more recent ones (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other coronaviruses like HCoV-NL63, HCoV-229E, HCoV-HKU1, and HCoV-O43 are known to cause mild respiratory disease in humans and also crossed the species barrier(57). Interestingly, the latter two viruses which cause more clinically mild disease appear to have derived from bovine coronavirus (BCoV)(810), which causes respiratory and intestinal disease in cattle (7,1113). Betacoronaviruses as a group have a wide host range including several agricultural and companion animal species(8).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the latter two viruses which cause more clinically mild disease appear to have derived from bovine coronavirus (BCoV)(810), which causes respiratory and intestinal disease in cattle (7,1113). Betacoronaviruses as a group have a wide host range including several agricultural and companion animal species(8). Thus, coronavirus disease in humans appears to largely be through zoonotic transfer and has resulted in enormous worldwide morbidity and mortality as well as significant economic loss.…”
Section: Introductionmentioning
confidence: 99%